Analysis on the Extreme Heat Wave over China around Yangtze River Region in the Summer of 2013 and Its Main Contributing Factors - Jin Li; Ting Ding; Xiaolong Jia; Xianchan Zhao (Advances in Meteorology)
In the summer of 2013, a rare extreme heat wave occurred in the middle and lower reaches of the Yangtze River in China. Based on high resolution reanalysis data from ECMWF, comprehensive analyses on the associated atmospheric circulation and the sea surface temperature anomaly (SSTA) were provided. The stable and strong West Pacific Subtropical High (WPSH) was the direct cause for the heat wave. The WPSH had four westward extensions, which brought about four hot spells in southern China. The South Asia High (SAH) at 150 hPa was more eastward and more northward than normal. The strong Hadley circulation in the central and western Pacific and the anomalous easterlies at 500 hPa and 250 hPa in the middle and high latitudes were favorable for more hot days (HDs). The total HDs in the middle and lower reaches of the Yangtze River had close relationships with the zonal wind anomalies in the middle and high latitudes, the SSTA in the Indian Ocean and Pacific, and the dry soil conditions of the Yangtze River Valley in spring and summer. The anomalies of the tropical, subtropical, and polar circulation and the underlying surfaces could be responsible for this extreme heat wave.